Natural gas hydrate accumulation mechanisms considering the multi-phase seepage and exploitation disturbance in porous media. (15th December 2022) - Sun, Huiru; Chen, Bingbing; Yang, Ziming; Song, Yongchen; Yang, Mingjun
Graphical abstract: Highlights: Effect of initial MH saturation on hydrate accumulation in a flow system is studied. Amount of MH reformation decreased with water mass fraction and hydrate saturation. Onset time of blockage is delayed 0.7 times when MH saturation is elevated 1.8 times. MH reformation accumulation act as a barrier to prevent gas overflow from reservoirs. Abstract: Pressure gradient is established in reservoirs when the depressurization method is applied to decompose natural gas hydrates (NGHs). When the local reservoir pressure is in the thermodynamically stable area, hydrate reformation and blockage may occur and lead to incomplete hydrate exploitation. However, studies have so far not focused on the effect of hydrate saturation change and multiphase flow at the different exploitation stages on NGHs production behaviors, thus, it was the research priority in this study. The NGHs saturation at different exploitation stages is characterized by controlling the initial hydrate saturation, and the multiphase flow in reservoirs is simulated by controlling the water–gas flowrate. The results show that the onset time of blockage and amount of hydrate reformation were negatively associated with initial hydrate saturation (Shi ) at a given water–gas flowrate. When the Shi elevated 1.8 times, the onset time of blockage and increment of hydrate saturation decreased by 0.7 times in the flow system. However, when the Shi < 12 %, the hydrate accumulation, and flow blockage were avoided with the water–gas flowrate of 10–1 mL/min. Other conditions being the same, the onset time of blockage was increased with the water phase fraction, while the increment of hydrate saturation was decreased with the water mass fraction. At a given gas flowrate of 1 mL/min and initial hydrate saturation of 40 %, when the water flowrate improved 7.5 times, a factor of 2.6 decreases in the increment of hydrate saturation was confirmed, from around 33.73 % to 12.95 %. Furthermore, the hydrate reformation and accumulation can prevent the gas overflow by forming the hydrate barrier, thus, a stable pressure was observed after flow blockage.